Otimização das propriedades mecânicas da liga de alumínio 319 contaminada com ferro - Freitas, Brenda Juliet Martins (2019)
The influence of iron additions (0.6, 0.8, 1.2 and 1.5 wt.%) and heat treatment on the microstructure and tensile properties of the 319-aluminum alloy processed by spray forming and rotary swaging was investigated. The spray-formed deposits were rotary swaged at 573 K with an area reduction ratio of 5:1. Room temperature tensile tests showed a substantial increase of elongation at fracture (5.5-8%) when compared to the values observed for the iron-containing conventionally cast counterpart (0.6%). The high values of elongation at fracture were obtained due to the significant microstructural refinement and decrease of volumetric phase fraction, especially the iron-rich intermetallics, promoted by the combination of spray forming and rotary swaging. Moreover, the heat treatment is responsible for the silicon globulization, dissolution of θ-Al2Cu blocks and dramatic improvement of ductility (16-17%).